Optimization of vegetative growth and sweet cassava yield through biostimulant and cultivation methods - Paolino, Thais Chavans [UNESP]; Rezende, Murillo Martins [UNESP]; Malenowtch, Joao Vitor Cordeiro [UNESP]; Carvalho, Alex Mendonca de [UNESP]; Teramoto, Erico Tadao [UNESP]; Ferrari, Samuel [UNESP] (Univ Federal Mato Grosso, 2023)
The intensification of production in the same area has instigated the development of new technologies. The present work aimed to evaluate the response in the vegetative and productive development of sweet cassava, compared to cultivation methods and plant hormones application. Two field experiments were conducted with sweet cassava cultivation. (a) First experiment -4 doses of plant bioregulator Stimulate (R) (0, 0.5, 1 and 1.5 L ha(-1) of the commercial product) applied in planting furrow on the stems of the white variety; and two modes of soil preparation, one being subsoiling and harrowing and the other without soil preparation. (b) Second experiment -4 doses of plant bioregulator Stimulate (R) (0, 0.25, 0.5, and 1.0 L ha(-1) of the commercial product); and two modes of application, the first in planting furrows on the yellow variety stems and the second in the foliar application at 90 days after planting (DAP). Planting sweet cassava without disturbing the soil indicates superiority in the quantity, length and roots yield, and greater weight of the aerial part. The use of biostimulant doses allowed greater vegetative development in height, diameter and weight of the aerial part, in addition to greater root length.
Keywords: manihot esculenta; plant hormones; soil tillage